PENENTUAN KELAY????AKAN CALON PENERIMA BANTUAN ????RTLH???? MENGGUNAKAN LOGIKA FUZZY MAMDANI DI DESA TANJUNG GLUGUR - Moh. Ridwan; Dahliatul Hasanah (UNIVERSITAS NEGERI MALANG, 2021)
One of the strategies to increase the quality of basic facilities of residential districts based on livable house indicators is to repair the targetted houses using the RTLH (Rumah Tidak Layak Huni) grant. The nominees of the grant have been decided by the village officials subjectively by observing from the data of previous grants. The appropriateness of the nominees, however, must be reconsidered firmly in order to have the program done as purposed. The concept of Mamdani fuzzy logic can be used to determine the appropriateness of the candidates. The method used in this research is quantitative research by using secondary data collected by village officials of Tanjung Glugur. This research has one output variable, the appropriateness of the candidates, and four input variables: residential buildings, water needs, sanitation and waste management, and income. The Fuzzy numbers that are used are triangular and shoulder fuzzy sets, while for the defuzzification four methods are used, which are the Smallest of Maximum (SOM), Mean of Maximum (MOM), Bisector, and Centroid. By analyzing the data result, similar results are obtained from all four methods. There are 57 out of 76 candidates who are stated as successful.